Pengaruh Motivasi, Disiplin dan Lingkungan Kerja Terhadap Kinerja Tenaga Pengajar Lembaga Pendidikan iSMART di Kota Palembang - Silvyana Silvyana; Trisniarty Adjeng Moelyatie; Maftuhah Nurrahmi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
This research aims to determine the influence of motivation, discipline, and work environtment on employee performance at Lembaga Pendidikan iSMART Palembang. Associative research methods with multiple linear regression and analysis technique. The sampling technique was simple sampling, by taking the entire sample of 115 respondents. The results showed that : (1) motivation, discipline and work environment partially significant effect on employee performance at Lembaga Pendidikan iSMART Palembang. (2) motivation, discipline and work environment simultaneously significant effect on employee performance of teachers at Lembaga Pendidikan iSMART Palembang